解方程(:x分之2)-(x-1分之1)=(2x-2分之3)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:23:06
解方程(:x分之2)-(x-1分之1)=(2x-2分之3)解方程(:x分之2)-(x-1分之1)=(2x-2分之3)解方程(:x分之2)-(x-1分之1)=(2x-2分之3)2/x-1/(x-1)=3
解方程(:x分之2)-(x-1分之1)=(2x-2分之3)
解方程(:x分之2)-(x-1分之1)=(2x-2分之3)
解方程(:x分之2)-(x-1分之1)=(2x-2分之3)
2/x -1/(x-1)=3/(2x-2)
乘以2x(x-1)得
2*2(x-1)-2x=3x
4x-4-2x=3x
2x-3x=4
-x=4
x=-4
经检验,x=-4是原方程的解
解方程2分之x+6分之x+12分之x+20分之x=1
x-1分之1=x分之2解方程
x-13分之x=2分之1 解方程
解方程;x+2分之1+x分之1=x^2+2x分之32
解方程x+1分之x=x分之2-x+1分之1
x^2-2x分之4+x分之1=x-2分之2 解方程
解方程:x分之2+x+1分之6=x(x+1)分之15
x分之1+(x+1分之1)=2x+2分之5 ,解方程,
解方程(:x分之2)-(x-1分之1)=(2x-2分之3)
解方程1+x分之2-1-x分之3=x-1分之6
x+1分之1+x-2分之2=x平方-4分之8解方程
解方程3分之2+3x-1分之x=9x-3分之1
解分式方程 2x-4分之3+2-x分之x=2分之1
解方程1*2分之x+2*3分之x+...+2010*2011分之x=2010
解方程1×2分之x+2×3分之x+...+2010×2011分之x=2010
解方程:1*2分之x+2*3分之x+.+2011*2012分之x=2011
解方程:3分之2X+4分之1X=3分之2 求X
解方程:三分之x-1-六分之x+2=二分之4-x